Sustainable Urban Development: Russian Experience - MURZIN, Anton (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019DO - 10.14505//jarle.v10.2(40).20, 2020)
Society has been studying city phenomenon since its origin. However, main factors of its sustainable development, which is top priority of strategic management and an indicator of management efficiency, has not been fully investigated. The present research purpose is to study factors and issues of stable development, generalization of Russian trends in city management in various socio-economic conditions. Development level of Russian cities was analyzed on the basis of integral indicator – sustainable development index, comprising structured complex of statistic rates, characterizing sustainable development along three sections: economic, ecological, and social. The author assesses effectiveness of strategic planning of large city development, points out drawbacks and targeted directions of management decisions, focused on city development with a number of result-oriented indicators. General tendencies of Russian agglomerations were supported by the results of assessing development sustainability of Russian cities. Perspective lines and criteria of strategic sustainable development have been identified, such as ‘smart’ services and technologies of city life.